The Educational Trajectories of Latina Teenage Mothers: How Do Certain Stressors and Supports Influence the Ability to Juggle Family Building and Educational Attainment? - Wright, Charlotte Anne (Tufts Archival Research Center, 2005)
Using data from the evaluation of a home-visiting evaluation program, the educational trajectories of first-time Latina mothers under the age of 21 will be examined and interpreted in this study. Why and how some of the Latina teenage mothers in the sample continue with their education while others discontinued will be explored by comparing the circumstances of fifteen young Latina mothers who stayed in school and on track, fifteen mothers whose education was interrupted and then resumed, and fourteen mothers who discontinued their education. An understanding of the common challenges that the Latina teenage mothers in the sample face and the kind of supports that may aid them in staying in school and "on track" is provided in this study through the examination of selected school and family-related stressors. Certain supports and stressors will be examined through a cultural lens in order to learn how the often, clashing cultural scripts of family building and educational attainment are successfully, or not successfully, juggled by participants in the present study. The objective of this study is to better understand the barriers that may challenge the graduation of Latina teenage mothers, and to recommend those supports that might facilitate overcoming of these barriers.